Spatial distribution of enteroparasites among school children from Guarapuava, State of Paraná, Brazil Distribuição espacial de enteroparasitas em crianças escolares na cidade de Guarapuava, Estado do Paraná, Brasil - Maria Luisa Tunes Buschini; Elaine Pittner; Tiago Czervinski; Ivonete de Fátima Moraes; Mônica Monteiro Moreira; Hermes Francisco Sanches; Marta Chagas Monteiro (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2007)
The most common infections in human beings are caused by intestinal parasites. They can lead to a number of harmful effects, which could include, among others, intestinal obstruction, malnutrition, iron deficiency anemia, diarrhea, and poor absorption. In Brazil, enteroparasites are one of the main public health issues. The present study aims at analyzing the distribution and frequency of enteroparasite occurrence in 635 children from seven community schools in the city of Guarapuava, Paraná (PR). In addition, we used similarity and diversity indices to analyze the parasite community. We found 475 samples with at least one parasite showing that 75.27% of children had enteroparasites. A smaller fraction (26.73%) of children harbored several parasites (multiparasitism), especially Giardia duodenalis (56%), and Ascaris lumbricoides (18%). Statistical analysis showed that three (out of seven) children communities had higher similarity in frequency and amount of parasites. Our results suggest that the children studied were highly infected by enteroparasites. These levels of infestation could be related to several factors, such as climate, social and economic conditions and characteristics of the parasites. As infecções mais freqüentemente encontradas em seres humanos são ocasionadas por parasitos intestinais, os quais podem causar danos aos hospedeiros, que incluem, entre outros agravos, a obstrução intestinal, desnutrição, anemia por deficiência de ferro, quadros de diarréia e de má absorção. No Brasil, as enteroparasitoses estão entre os principais problemas de saúde pública. Este trabalho teve como objetivo avaliar a distribuição e freqüência de enteroparasitos em 635 crianças pertencentes a sete comunidades escolares do município de Guarapuava - PR. Além disso, verificar índices de similaridade e diversidade de parasitas nas comunidades. Nos resultados, foram encontradas 475 amostras positivas para pelo menos um parasito, cuja prevalência de enteroparasitoses nesta população foi de 75,27 % e a ocorrência de casos de poliparasitismo de 26,73 %, dos quais foram registrados maiores índices de infecções por Giardia duodenalis (56 %) e Ascaris lumbricoides (18 %). A análise estatística mostrou que três das sete comunidades avaliadas apresentaram maior índice de similaridade quanto à freqüência e carga parasitária. Nossos resultados sugerem que as crianças avaliadas apresentavam altos índices de infecção por enteroparasitas e que fatores como clima, condições sociais e econômicas da população estudada e características próprias do parasito podem estar facilitando o acometimento destes indivíduos.